2020
DOI: 10.1088/1748-9326/ab865a
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing clean cooking options in peri-urban Kenya: a pilot study of advanced gasifier stove adoption

Abstract: Kenya has experienced a decade of relative prosperity with consistent economic growth and minimal political tension. GDP is growing by 3% annually and poverty rates are declining. Despite these gains, Kenya still has a lot of ground to cover to achieve the Sustainable Development Goals (SDGs) by 2030. SDG7, which aims to ‘Ensure access to affordable, reliable, sustainable and modern energy for all’, exemplifies both Kenya’s achievements and the challenges that remain. Access to grid-based electricity and LPG h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…A recent intervention study assessing the acceptability of PAYG payments for pellets (with gasifier stoves) in peri-urban Kenya found that PAYG displaced traditional fuels in many households, and participants had higher willingness to pay for PAYG technology, compared with non-PAYG stoves. 44 Participants not interested in registering for PAYG LPG in the study community had higher average monthly incomes than the study population average, suggesting that the barrier of LPG affordability addressed by PAYG LPG was of less relevance to these households. Nevertheless, 52% of LPG primary users were interested in registering for PAYG LPG technology because of other advantages, including perceived increased safety (27%), customer service (13%) and the ability to monitor their LPG usage (12%).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…A recent intervention study assessing the acceptability of PAYG payments for pellets (with gasifier stoves) in peri-urban Kenya found that PAYG displaced traditional fuels in many households, and participants had higher willingness to pay for PAYG technology, compared with non-PAYG stoves. 44 Participants not interested in registering for PAYG LPG in the study community had higher average monthly incomes than the study population average, suggesting that the barrier of LPG affordability addressed by PAYG LPG was of less relevance to these households. Nevertheless, 52% of LPG primary users were interested in registering for PAYG LPG technology because of other advantages, including perceived increased safety (27%), customer service (13%) and the ability to monitor their LPG usage (12%).…”
Section: Discussionmentioning
confidence: 90%
“…Two-thirds of current kerosene users reported an intention to register with a PAYG LPG company (30%) or being interested in learning more about the technology (35%) (Table 2). A recent intervention study assessing the acceptability of PAYG payments for pellets (with gasifier stoves) in peri-urban Kenya found that PAYG displaced traditional fuels in many households, and participants had higher willingness to pay for PAYG technology, compared with non-PAYG stoves 44 …”
Section: Discussionmentioning
confidence: 99%
“…Some studies consider fuel expenditure per day [91,92], fuel cost per month [93,94] or total costs per year [32,95] (which may include investment, fuel cost, useful life of system, efficiency, and total fuel purchased) [71,96]. In LPG studies from South Africa, Brazil, and Kenya, a clean fuel study from Ghana and Uganda, and India's CEEW report, fuel efficiency was taken into account to produce cost per fuel unit rather than cost per fuel weight [50,86,[97][98][99]. Efficiency also affects cost per meal metrics of affordability [100,101].…”
Section: Thresholdsmentioning
confidence: 99%
“…4). LPG's higher energy density prohibits researchers from comparing fuels using cost per weight metrics [99]. Some studies evaluate affordability of different fuels by comparing each fuel's per unit metrics and implicitly define a fuel as affordable if its per unit metrics are cheaper than the alternatives in use.…”
Section: Thresholdsmentioning
confidence: 99%
“…a WISDOM gasi er stove costed US$ 34) [3]. Other factors also affect the adoption of pellet gasi er cookstoves, and households will generally adopt a fuel stacking model [24][25][26][27][28][29][30]12]. Ongoing pellet production and gasi er cookstoves initiatives in Kenya include: Lean Energy Solutions Ltd., Iko Briq Ltd., Power Spot Ltd., Wisdom Innovations Ltd., and KIRDI [3,10,31,32].…”
Section: Introduction 11 Backgroundmentioning
confidence: 99%